Métalittératie et pensée critique de futurs enseignants : pratiques et perceptions en francophonie - Florent Michelot; Bruno Poellhuber; Sébastien Béland (Revue Internationale de Pédagogie de l’Enseignement Supérieur, 2023)
Critical thinking and the ability to deal with information appeared to be crucial in the last few years, especially given the deleterious role of social media, real or perceived. To address this issue, the role of education and, therefore, of teachers, appears to be central. In this article, we present observations made on preservice teachers in an activity including video viewing and debate on a Facebook social group. Using screen-casting and a protocol requesting thinking aloud, we were able to document the critical thinking practices and metaliteracy (a concept encompassing skills such as informational and digital literacies) strategies of preservice teachers in Wallonia, France and Québec (n = 9). Through a series of interviews (n = 32), we could contrast these strategies with those reported as known. Students in vocational training would more likely mobilize metacognitive and self-critical strategies whereas those in disciplinary training would rather mobilize so-called criterion-referenced strategies. Regardless of the type of training, there are fewer mobilized strategies than known strategies.